Vulture declines, threats and conservation: the attitude of the indigenous Ghanaian. Issue 1 (8th March 2020) - DEIKUMAH, JUSTUS P.
Summary: Understanding the attitude of people towards vultures, especially factors that influence behaviours that support their conservation, is crucial if the decline in vultures is to be slowed and reversed. Their vital ecosystem function in keeping the environment free of carcasses and reducing the spread of disease is not yet appreciated in Ghana. Little is known about the attitude of Ghanaians' about vultures. Structured questionnaires and key informant surveys were employed with a sample size of 460 respondents randomly selected across Ghana. Over 85% of respondents were familiar with the Hooded Vulture Necrosyrtes monachus and vultures were culturally important to 56% of respondents. Diseases that affect livestock are claimed to be treated with chemicals such as diclofenac sodium to which vultures are highly susceptible globally and livestock carcasses were not available to vultures as 53% of respondents bury carcasses. A new poisoning pathway has emerged in which furadan is used to poison wildlife for bushmeat and the offal removed which is then consumed by vultures, as indicated by 78% of respondents. The majority of respondents positively thought vultures were important and must be protected. Poisoning, habitat loss particularly the loss of silk cotton tree Ceiba pentandra and trade in vulture parts for traditional medicine are major threats to vultures in Ghana. Continuous awareness creation, positive attitude towards the environment, vulture conservation programmes and protection of breeding sites were some urgent conservation actions recommended to ensure the survival of vultures.